Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've been trying to add math rigor to a solution of the functional equation in [1], eq. (22). It is: $$ f\left(\frac{x}{f(x)}\right) = \frac{1}{f(x)}\,, $$ where you know that $f(0)=1$ and $f(-x) = f(x)$.

I've been trying to fill in the missing steps. Let's use a substitution $g(x) = \frac{x}{f(x)}$. So we rewrite the functional equation as $$ x = \frac{\frac{x}{f(x)}}{f\left(\frac{x}{f(x)}\right)} $$ and get $$ x = g(g(x))\,. $$ Then we calculate $g'(0)$ as follows: $$ g'(0) = \left.\left(\frac{x}{f(x)} \right)'\right|_{x=0} = \left.\frac{f(x)-xf'(x)}{f^2(x)}\right|_{x=0} = \frac{f(0)}{f^2(0)} = 1\,. $$ Also we can use that $g(x)$ is odd $$ g(-x) = \frac{-x}{f(-x)} = -\frac{x}{f(x)} = -g(x)\,. $$ Whenever $g(g(x)) = x$, I have found that this is called involution. That can have many solutions, but using $g(-x)=-g(x)$ and $g'(0)=1$, there should be a way to prove that $g(x) = x$, from which $f(x)=1$ as the only solution.

The article [1] just says, that since $g(x) = g^{-1}(x)$, the graph of $g(x)$ and its inverse must be symmetric along the $y=x$ axis, and since the tangent at $x=0$ is equal to this same line, then $g(x)=x$ must be the only solution. They do mention that this is not completely rigorous proof.

You can assume that $f(x)$ is differentiable. It'd be nice if it can be proven only for continuous functions $f(x)$, but any proof at first would be a good start, even with stronger assumptions.

Update: another idea is to use the fact, that if $a$ and $b$ are two points in the domain of the $g$ function for which $g(a)=g(b)$, then it follows that $g(g(a)) = g(g(b))$ and $a = b$, which proves that the function is one-to-one. Given that $g$ is continuous, it means that it is strictly increasing or decreasing [2]. From that, let's say it's increasing, then we can use $y=g(x)$, if $y < x$, then $g(y) < g(x)$ from which $g(g(x)) < y$ and $x < y$ which is a contradiction. Similarly for $y > x$. So we must have $y=x$, from which $g(x)=x$. If $g$ is decreasing, then we set $h(x)=-g(x)$, obtain $h(x)=x$ and $g(x)=-x$. Unless I made a mistake we got $g(x)=\pm x$. And using $g'(0)=1$, we get $g(x)=x$ as the only solution. But I don't feel very good about this proof yet.

[1] Levy-Leblond, J.-M. (1976). One more derivation of the Lorentz transformation. American Journal of Physics, 44(3), 271–277.

[2] A continuous, injective function $f: \mathbb{R} \to \mathbb{R}$ is either strictly increasing or strictly decreasing.

share|improve this question
1  
Because $g(x)=1/x$ is also a solution of $g(g(x))$ and somehow it got eliminated. So something is not right. (Of course, it would get eliminated later anyway due to $g'(0)=1$, but that's not the point.) –  Ondřej Čertík Jan 16 '13 at 7:58
1  
Because $g(x)=1/x$ is not defined on $\mathbf R$, only on $\mathbf R^*$. Notice that it's also neither increasing nor decreasing. The answer you linked to uses the intermediate value theorem, which you can only apply on an interval, and $\mathbf R^*$ is not an interval. –  jathd Jan 16 '13 at 8:01
2  
Your proof in your update is almost certainly exactly what the authors had in mind, but didn't type out. Briefly: if $g$ is not $x\mapsto x$, then there is some $h>0$ such that $g(h)$ is close to $h>0$, yet $g(h)\neq h$. Then the reflection of the point $(h,g(h))$ will be on the other side of the line $y=x$, contradicting the monotonicity of the function.$\Box$ –  Samuel Jan 16 '13 at 8:13
1  
Two things. For the increasing case, you assume (without saying it) that $g$ is defined on an interval $I$, and that $g$ sends $I$ into $I$ (because you use $y<x\Rightarrow g(y)<g(x)$), which explain $g(x)=-1/x$ on $(0,\infty)$. The other thing is that for the decreasing case, you set $h(x)=-g(x)$, and if you write that case in detail you'll see that you use $g(-x)=-g(x)$, which you can't say about $g(x)=1/x$ on $(0,\infty)$, because if $x\in(0,\infty)$ then $-x\notin(0,\infty)$. –  jathd Jan 16 '13 at 8:13
1  
Given that $f(x)$ is symmetric, you also know that all odd derivatives of $1/f(x/f(x))$ are zero. If you manage to express th even ones, $(1/f(x/f(x)))^{(2n)}$, analytically, you might get some information out, maybe even conclude that all are zero such that $f(x)=1$. –  NikolajK Jan 16 '13 at 13:07

3 Answers 3

Hmm, it seems to me that the only solution is the constant function $f(x)=1$
Let's assume that $f(x)$ has a power series, then

  • the constant term must be 1, because $f(0)=1$
  • we have only nonzero coefficients at the powers of x where the exponents are even because $f(x)=f(-x)$

so we assume $$f(x) = 1 + ax^2 + bx^4 + cx^6 + O(x^8) $$ Then for the rhs of your defining equation we have $$ {1 \over f(x)} = 1 - ax^2 + (a^2-b) x^4 + (-c + (-a^3 + 2ba)) x^6 + O(x^8) $$ For the lhs of your defining equation we have $$ f(x {1 \over f(x)}) = 1 + ax^2 + (b -2 a^2)x^4 + (c + 3 a^3 - 6ab) x^6 + O(x^8) $$ and equating coefficients requires

  • $a=0 \to (f"(0)=0) $ and
    then $ \qquad \qquad {1 \over f(x)} = 1 -b x^4 -c x^6 + O(x^8) $
    must equal $ f(x {1 \over f(x)}) = 1 + b x^4 + c x^6 + O(x^8) $
  • thus is required that $b=0 \to f^{(4)}(0)=0 $ and
    then $ \qquad \qquad {1 \over f(x)} = 1 -c x^6 + O(x^8) $
    must equal $ f(x {1 \over f(x)}) = 1 + c x^6 + O(x^8) $
  • thus is required that $c=0 \to f^{(6)}(0)=0 $ ...

... and I assume, that all following coefficients must equal zero. Thus: the only solution should be $$f(x)=1$$ and your $$g(x)={x \over f(x)}=x$$

share|improve this answer
    
Very nice! So if the function $f(x)$ is analytic, then you prove that $f(x)=1$. Assuming only that $f(x)$ is continuous, then the only possible other solutions are not analytic. That helps a lot. –  Ondřej Čertík Jan 16 '13 at 16:15
    
The constant function $-1$ works too. –  alex.jordan Jan 15 at 15:19

Some results described above.
(i) $g$ is monotone.
(ii) $g$ = $g^{-1}$
(iii) $g$ is odd.
(iv) $g$ differentiable at $0$
Summary:
Suppose $g$ is not the identity. Then for $\forall r$, we know $g$ has a symmetrical counterpart to $g(r)$ w.r.t. $y=x$ from (ii). Now consider, $(r,g(r))$ for $r>0$ and his symmetric counterpart. Later consider $(-r,g(-r))$ and his symmetric counterpart. There is no way to ensure monotonicity between these coordinates for, in any case, the points will form a rectangle with two sides parallel and two perpendicular to $y=x$. So in adhering to the symmetry, $g$ must either fail to be a function or $g$ must violate monotonicity somewhere by crossing $y=x$. So $g$ must be the identity. Thus $f=1$.

share|improve this answer

Given what you have already established, it will suffice to show that if $g$ is a continuous function with $g(g(x)) = x$, and $g(0) = 0,\ g'(0) = 1$, then $g(x) = x$ for all $x$. (Note that $g'(0) = 1$ because $g(x) = x + x(\frac{1}{f(x)} - 1) = x + o(x)$, using only continuity of $f$ at $0$).

Clearly, $g$ is injective: If $g(x_0) = g(x_1)$ then $x_0 = g(g(x_0)) = g(g(x_1)) = x_1$.

Thus, $g$ is monotonous: If it were not, it would have a local extreme at some $x_0$, and would not be injective in the neighbourhood of $x_0$. Because $g$ is increasing at $0$, it is therefore increasing on the whole domain.

We will now show that $g(x) = x$ for all $x$. Clearly, this holds for $x=0$. For a proof by contradiction, suppose that we have $x_0$ with $g(x_0) \neq x_0$. Let $x_1 := g(x_0)$. Then $x_0,x_1$ are distinct, and $g$ ''swaps'' these two points: $g(x_0) = x_1,\ g(x_1) = x_0$. Suppose without loss of generality that $x_0 < x_1$. We have $g(x_0) = x_1 > x_0 = g(x_1)$. But this contradicts the assumption that $g$ is increasing. Thus, we indeed have $g(x) = x$ for all $x$. $\square$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.